2011
DOI: 10.1681/asn.2010070701
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Signaling Maintains the Epithelial Phenotype of Proximal Tubular Cells

Abstract: Epithelial-mesenchymal transition (EMT) contributes to the progression of renal tubulointerstitial fibrosis. The N-methyl-D-aspartate receptor (NMDAR), which is present in proximal tubular epithelium, is a glutamate receptor that acts as a calcium channel. Activation of NMDAR induces actin rearrangement in cells of the central nervous system, but whether it helps maintain the epithelial phenotype of the proximal tubule is unknown. Here, knockdown of NMDAR1 in a proximal tubule cell line (HK-2) induced changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 59 publications
5
55
0
Order By: Relevance
“…and increased motility [20][21][22] . To investigate the effect of VEGF on EMT in the kidney, α-SMA and E-cadherin protein and mRNA expression levels were determined by Western blot and RT-PCR, respectively, in UUO mice treated with or without VEGF.…”
Section: Vegf Improves Histopathologic Changes In Uuo Micementioning
confidence: 98%
“…and increased motility [20][21][22] . To investigate the effect of VEGF on EMT in the kidney, α-SMA and E-cadherin protein and mRNA expression levels were determined by Western blot and RT-PCR, respectively, in UUO mice treated with or without VEGF.…”
Section: Vegf Improves Histopathologic Changes In Uuo Micementioning
confidence: 98%
“…Reverse transcription and real-time PCR were performed as described. (36) Briefly, real-time PCR with gene-specific TaqMan probes for rat and mouse VDR, 1a-hydroxylase, 24-hydroxylase, RUNX2, and GAPDH as an endogenous control (Applied Biosystems, Foster City, CA, USA) was performed with an ABI Prism 7000 Sequence Detection System (Applied Biosystems) using TaqMan Universal PCR Master Mix. Forty cycles at 95°C for 15 sec and 60°C for 1 min were performed.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…When RPTECs are injured, these intercellular links are disrupted and b-catenin relocalizes into the nucleus after structural reconfiguration (Gottardi & Gumbiner, 2004). It then associates with the TCF/LEF complex and rules the transcription of several genes, notably those involved in fibrosis (Bozic et al, 2011). Research has suggested that inhibiting the b-catenin pathway restrains the progression of renal fibrosis (Hao et al, 2011;He et al, 2011).…”
Section: Reduction Of Collagen Synthesismentioning
confidence: 99%